Characterization of a large cohort of patients with unclassified bleeding disorder; clinical features, management of haemostatic challenges and use of global haemostatic assessment with proposed recommendations for diagnosis and treatment. (20th November 2019) - MacDonald, Stephen; Wright, Alfie; Beuche, Frederik; Downes, Kate; Besser, Martin; Symington, Emily; Kelly, Anne; Thomas, Will
Abstract: Introduction: There is an unmet need to characterize the diagnosis and management of patients with an unclassified bleeding disorder (UBD). Methods: Retrospective review of registered patients with UBD at our centre. Assessment including rotational thromboelastometry (ROTEM) and thrombin generation (TG) were used. Results: A total of 124 patients were identified; 91% female. Mean age of presentation was 38.3 years. Mean bleeding score was 8.8 (standard deviation [SD] 3.8); 6.6 in men (SD 1.4) and 9.7 in women (SD 3.3), which was significantly different ( P  < .05). In women, after deduction of scores for menorrhagia and postpartum haemorrhage, the mean score was 6.4 which was not significantly different to the male score ( P  = .11). Twenty‐three percent of patients have been transfused, 61% women had treatment for menorrhagia and 17% for epistaxis. TxA and desmopressin were effective at preventing bleeding in 69 procedures and 13 deliveries. TG revealed 26% patients with a long lag time and 19% with a decreased endogenous thrombin potential but no diagnostic pattern was seen. ROTEM (NATEM) was unable to characterize patients; 9% had a prolonged clot time or maximum lysis. ThromboGenomics was normal in 45 tested patients. Conclusions: We provide data which shows the bleeding score is biased towards gynaecological bleeding but which remains elevated even when the bleeding score is deducted. Tranexamic acid and desmopressin are effective as haemostatic prophylaxis but there is an urgent need for clinical trials. In conclusion, we describe the use of the bleeding score in these patients and phenotype, diagnosis (including ThromboGenomic testing) and management with practice recommendations.